Optimization of Biogas Liquid Waste from Livestock Manure as a Source of Renewable Energy through Microbial Fuel Cell (MFC) Technology - Alwahab, Alwahab; Maharani, Pratitis Tri; Nur K., Wa Ode Miranda; Ahmad, La Ode; Alimin, Alimin; Zaeni, Ahmad (Universitas PGRI Semarang, 2024)
This study examines the potential of biogas effluent as a source of electrical energy through microbial fuel cell (MFC) technology. The results showed that the one-room MFC produced a maximum voltage of 1302,2 mV, while the two-room MFC with KMnO4 electrolyte reached 1084,3 mV with an electric current of 0,1 mA. Simultaneously, the two-chamber MFC with K2Cr2O4 produced a maximum voltage of 1675,8 mV and an electric current of 0,99 mA. This potential, with electrical voltage values equivalent to commercial batteries, can improve the efficiency of electrical energy generation from organic waste and open up wider application opportunities in using renewable energy sources. Characterization of the MFC substrate showed a decrease in organic matter of biogas effluent with COD values of 500,96 mg/L and BOD of 300,23 mg/L. MFC bacteria from biogas waste were dominated by Gram-positive rod-shaped and Sarcina, except for one Gram-negative isolate of Spirillum.